2020
DOI: 10.1101/2020.02.19.956672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chronic stress exacerbates acute stress-induced neuronal activation in the anterior cingulate cortex and ventral hippocampus that correlates with behavioral deficits in mice

Abstract: Altered activity of corticolimbic brain regions is a hallmark of stress-related illnesses, including mood disorders, neurodegenerative diseases, and substance abuse disorders. Acute stress adaptively recruits brain region-specific functions for coping, while sustained activation under chronic stress may overwhelm feedback mechanisms and lead to pathological cellular and behavioral responses. The neural mechanisms underlying dysregulated stress response and how they contribute to behavioral deficits are poorly … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 129 publications
1
0
0
Order By: Relevance
“…Taken together, the findings in the present experiment demonstrated that CRS led to reduced body weight in stress group compared to control in consistent with previous studies [34] . Furthermore, many studies focused on the impact of stress or various stressors on testicular hormone production [35] , [36] .…”
Section: Discussionsupporting
confidence: 94%
“…Taken together, the findings in the present experiment demonstrated that CRS led to reduced body weight in stress group compared to control in consistent with previous studies [34] . Furthermore, many studies focused on the impact of stress or various stressors on testicular hormone production [35] , [36] .…”
Section: Discussionsupporting
confidence: 94%